Comparison Of Media Framing Of The Cancellation Of Ferdy Sambo's Death Sentence On Online News Portals In Indonesia - Hanif, Raden Muhammad Ciptaning; Bajari, Atwar; Wibowo, S. Kunto Adi (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2025)
The online news portal covering the case of Ferdy Sambo's death sentence being overturned is one example of an issue that has received widespread attention from the public and the media. Differences in media framing of this issue can influence public perception and shape public opinion. Therefore, this study aims to compare the media framing of the news coverage of Ferdy Sambo's death sentence cancellation on the online news portals detik.com and kompas.com. Using content analysis and the framing model of Semetko Valkenburg, this study compares the perspectives of the news based on five framing elements: Conflict Frame, Economic Consequences, Human Interest Frame, Responsibility Frame, and Morality Frame. This study also uses a positivistic paradigm and deductive method to analyze the events surrounding Ferdy Sambo's death sentence through two leading online media outlets in Indonesia. The results of the study show significant differences in the use of the Conflict, Human Interest, Responsibility, and Morality frames between (detik.com) and (kompas.com), but there are no significant differences in the use of the Economic Consequences frame.